Protein turnover during in vitro tissue engineering. (March 2016) - Li, Qiyao; Chang, Zhen; Oliveira, Gisele; Xiong, Maiyer; Smith, Lloyd M.; Frey, Brian L.; Welham, Nathan V.
Abstract: Repopulating acellular biological scaffolds with phenotypically appropriate cells is a promising approach for regenerating functional tissues and organs. Under this tissue engineering paradigm, reseeded cells are expected to remodel the scaffold by active protein synthesis and degradation; however, the rate and extent of this remodeling remain largely unknown. Here, we present a technique to measure dynamic proteome changes during in vitro remodeling of decellularized tissue by reseeded cells, using vocal fold mucosa as the model system. Decellularization and recellularization were optimized, and a stable isotope labeling strategy was developed to differentiate remnant proteins constituting the original scaffold from proteins newly synthesized by reseeded cells. Turnover of matrix and cellular proteins and the effects of cell–scaffold interaction were elucidated. This technique sheds new light on in vitro tissue remodeling and the process of tissue regeneration, and is readily applicable to other tissue and organ systems.